2020
DOI: 10.1111/ics.12607
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vehicle on skin absorption of Mg2+ and Ca2+ from thermal spring water

Abstract: OBJECTIVE: Thermal spring waters (TSW) are commonly used as active ingredients in cosmetics. Their biological activities directly depend on the ionic composition of the spring. However, in order to exhibit beneficial properties, the minerals need to reach viable skin layers. The present study addresses the incorporation of marketed TSW in model cosmetic formulations and the impact of the formulation on skin absorption of magnesium and calcium ions that are known to improve skin barrier function. METHODS: Marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Tarnowska et al ( 2020 ) conducted skin penetration studies to define skin absorption profiles of Mg 2+ and Ca 2+ in cosmetics using thermal spring waters (TSW) as active ingredients. The skin absorption of these cations was studied using in vitro static Franz diffusion under infinite dose conditions and with occlusion of the apparatus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tarnowska et al ( 2020 ) conducted skin penetration studies to define skin absorption profiles of Mg 2+ and Ca 2+ in cosmetics using thermal spring waters (TSW) as active ingredients. The skin absorption of these cations was studied using in vitro static Franz diffusion under infinite dose conditions and with occlusion of the apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of using thermal waters as active ingredients in cosmetic formulations are influenced by the skin’s exposure to cations, specifically Mg 2+ and Ca 2+ , which exert more biological functions on the skin than anions. The dependency of benefits is intricately linked to the cosmetic formulation model, impacting the absorption and distribution of these active and beneficial cations across different skin layers (Tarnowska 2020 and authors therein).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, our last study carried on viable porcine skin explants demonstrated measurable absorption of Ca 2+ and Mg 2+ from a marketed TSW. Both cations diffused through the skin samples after direct application of TSW and when the TSW was incorporated into model cosmetic formulations (Tarnowska et al, 2020).…”
Section: Composition Of Thermal Spring Watersmentioning
confidence: 99%